Diseño de un sistema de evacuación y limpieza de emisiones en el proceso de fundición de plomo secundario en la empresa Recuperación de Metales S.A. (2017)
The project began with the identification of the problem, the current situation of the process and the existing air cleaning system was diagnosed, and alternatives to the design of the evacuation and cleaning system were then proposed and evaluated. After due consideration of the different alternatives, we proceeded to develop the detailed engineering of the alternative that was most appropriate. The different skills acquired in the career were applied to develop calculations and execute design drawings.